CHARACTERISTICS, ATTITUDES, AND PREFERENCES OF MISSOURI'S SPRING TURKEY HUNTERS - Larry D. Vangilder; Steven L. Sheriff; Gail S. Olson (Wildlife Society Bulletin)
Abstract: A questionnaire entitled “Turkey Hunting in Missouri” was sent to 7,000 randomly selected 1988 spring turkey hunting permit buyers to determine the characteristics, attitudes, and preferences of turkey hunters toward wild turkeys (Meleagris gallopavo silvestris), turkey hunting, and turkey harvest management. The composite Missouri spring turkey hunter was male, 39 years old, had a rural or small‐town background, and had hunted turkeys in Missouri in the spring for 7 years. Most hunters were satisfied with the quality of their 1988 spring season and experienced few problems with interference by other hunters (72.9%), all‐terrain or off‐road vehicles (88.8%), trespassing (80.5%), or free‐ranging dogs (79.1%). Most respondents (74.6%) thought Missouri's spring season was about the right length and preferred the current 14‐day season to a longer season if a longer season would mean a decrease in the proportion of adult gobblers in the harvest. Over 80% of the hunters derived great enjoyment from killing an adult gobbler while only about 25% derived great enjoyment from killing a juvenile gobbler. Missouri turkey hunters were concerned about being shot by another hunter and over 35% had been in a situation in which they believed they were in danger of being shot. Hunters opposed (82.3%) a mandatory hunter‐orange requirement, however, and most did not use orange while turkey hunting.